ANALISIS PERBEDAAN BUDAYA ORGANISASI ANTARA SEKTOR PUBLIK DAN SWASTA - Rangga; Muhammad Padillah; Yusuf Vedi Velandi; Wahjoe Pangestoeti (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the differences in organizational culture between the public and private sectors in Indonesia. Organizational culture is a crucial aspect that influences work effectiveness, employee satisfaction, and the quality of organizational services and products. The study uses a comparative quantitative approach with a total of 120 respondents, consisting of 60 public sector employees and 60 private sector employees. Data collection was carried out using an organizational culture questionnaire developed based on the theories of Hofstede and Schein. The findings reveal significant differences in the dimensions of organizational culture between the two sectors. The public sector tends to emphasize hierarchy and clan dimensions, while the private sector shows dominance in market and adhocracy dimensions. These results indicate that the public sector prioritizes stability, procedural compliance, and organizational loyalty, while the private sector is more flexible, competitive, and innovation-oriented. These differences have implications for organizational effectiveness, particularly in terms of work efficiency, employee job satisfaction, and adaptability to external changes. Therefore, public sector institutions must undergo cultural reform to align with the demands of modern management and achieve responsive and adaptive governance